A comparison of choroidal thicknesses between pachychoroid and normochoroid eyes acquired from wide‐field swept‐source OCT. Issue 1 (22nd June 2020) - Lim, Hyung Bin; Kim, Kyeungmin; Won, Yeo Kyoung; Lee, Woo Hyuk; Lee, Min Woo; Kim, Jung Yeul
Abstract: Purpose: We investigated the wide‐field choroidal thickness (CT) using swept‐source optical coherence tomography (SS‐OCT) and compared the characteristics of the choroidal layer between pachychoroid and normochoroid groups. Methods: A total of 120 eyes from 120 normal subjects were included. All subjects were divided into two groups according to the subfoveal CT (≥300 μm, pachychoroid group; <300μm, normochoroid group). All subjects underwent an HD spotlight 16 mm scan using SS‐OCT. The CT was measured at the following 12 points: subfoveal, 3 points in the nasal peripapillary area, 6 points in the macular area and 2 peripheral points at 5400 and 8100 µm from the fovea. The CT measurements were compared between the two groups, and statistical analyses were performed to determine clinical factors associated with each point of the CT. Results: The CT in the pachychoroid group was thicker than that in the normochoroid group at all points (p < 0.01). The CTs of the two groups in the macular area were highly associated with the subfoveal CT. However, the CTs of the nasal peripapillary and peripheral areas showed lower associations with the subfoveal CT and lower diagnostic abilities for the pachychoroid group. The existence of pachyvessels was found to be a significant factor causing the regional variations. Conclusions: The CTs in the peripapillary and peripheral areas showed different patterns than the subfoveal CT. Regional variations by pachyvessels were more frequent in the peripapillary and peripheral areas than in the macular area, and the subfoveal CT did not represent the whole choroidal area.